Variations of Phenomenon and Circumstance in Mental Processes - Gartika Rahmasari; Iis Kurnia Nurhayati (English Journal Literacy Utama, 2020)
This research aims to identify the variation of Phenomenon and Circumstance in mental processes. Data was taken from two literary works, and were analyzed using theories of Systemic Functional Linguistics by Halliday (1985), Thomas Bloor and Meriel Bloor (1995), and Egginns (2000). The analysis was conducted using content analysis method by sorting mental processes that contain two clauses where the second clause was projected by the first clause. Data was presented by identifying elements in mental processes containing Phenomenon and Circumstance. The main components of mental process include Participant, Process, and Phenomenon, with Circumstance as an optional component, meaning it is not an obligatory component in the processes. Results show that there are two variations of phenomenon that can project other clauses complemented by many types of Circumstance. The first is the phenomenon of Fact embedded with Circumstance of Location, Extent, Manner, and Matter. The second is the Phenomenon of Thought with Circumstance of Extent, Location, Manner, Cause and Role. The most frequent Circumstance that can be found includes Circumstance of Manner, followed by Circumstance of Extent.